2009
DOI: 10.1583/09-2717.1
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment for Chronic Type B Dissection:Limitations of Short Stent-Grafts Revealed at Midterm Follow-up

Abstract: Endovascular stent-graft treatment is effective therapy for chronic type B dissection patients with false lumen aneurysms. Erosion of the dissection membrane, causing proximal or distal endoleak, is the most common reason for re-intervention during midterm follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 10 publications
0
31
0
Order By: Relevance
“…Recent data on endovascular repair of chronic complicated TBAD reveal excellent procedural and survival outcomes, but at the expense of further re-interventions. The rates of stroke following endovascular-based repair ranged between 0% to 5%, it was 0% to 2% for paraplegia, up to 14% procedure-related mortality (20)(21)(22)(23)(24)(25)58,60,(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74) (Table 7).…”
Section: Medical Managementmentioning
confidence: 99%
“…Recent data on endovascular repair of chronic complicated TBAD reveal excellent procedural and survival outcomes, but at the expense of further re-interventions. The rates of stroke following endovascular-based repair ranged between 0% to 5%, it was 0% to 2% for paraplegia, up to 14% procedure-related mortality (20)(21)(22)(23)(24)(25)58,60,(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74) (Table 7).…”
Section: Medical Managementmentioning
confidence: 99%
“…In the case of replacement of the descending thoracic aorta, the intercostal arteries were usually not reconstructed, except in patients with Marfan syndrome. However, in the case of replacement of the thoracoabdominal aorta, [2][3] pairs of intercostal arteries between Th8 and L3 were reconstructed. The flow rate in the lower body was approximately 2.0 l·min -1 ·m 2 during distal clamping.…”
Section: Operative Techniquesmentioning
confidence: 99%
“…Although early and midterm results show that endovascular treatment is effective, new intimal tears occur at the end of the stent graft because of narrowness and limited flexibility of the true lumen; these tears lead to re-intervention or rupture during the follow-up period. [1][2][3] Recently, Xu et al reported that to avoid a proximal endoleak, the distance between the entry tear and opening of the left subclavian artery should be more than 10 mm. Furthermore, to avoid a distal endoleak, they recommended the use of a tapered stent graft.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Endograft erosion through the dissection septum has been described, mandating long-term follow-up. 14,15 This problem may be related to oversizing as well as to grafts with bare metal extensions.…”
Section: Demographicsmentioning
confidence: 99%